Morphological Development Characteristics of Cirques in the Western Kunlun Mountains - Jing Tao (E3S Web of Conferences)
Cirques, as typical representatives of glacial erosion landforms, serve as important indicators for reconstructing paleoclimate and paleoenvironments. Current research on cirque morphology in the western Kunlun Mountains remains limited, hindering a comprehensive understanding of cirques in this region. This study focuses on the western Kunlun Mountains in the Tibetan Plateau, extracting morphological parameters (length L, width W, height H, area Area, floor elevation E-min, etc.) of 75 cirques based on high-resolution remote sensing imagery. The results indicate a coordinated growth of morphological parameters during cirque development, with the highest proportion of cirques facing northeast (NE). The distribution of cirque orientations is relatively concentrated, and cirques at higher altitudes tend to be larger in size. This research fills a gap in the study of cirques in the western Kunlun Mountains and provides new insights for paleoclimate reconstruction in the region.